Analisis Manajemen Risiko Pada Aplikasi SAP LOGON 750 di PT. XYZ Berbasis ISO 31000:2018 - Budiono, Marvel Evandi; Haryani, Endang (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
The SAP LOGON 750 handles production process activities from inputting production data, production scheduling, production processes, to reporting production. There are various possible risks that occur, but PT. XYZ has never managed risks internally. This study aims to analyze risk management for the use of the SAP application. This research focuses on one case study object and applies a qualitative approach based on the ISO 31000: 2018 framework. The results found 18 possible risks. There are 12 medium level risks, among others are dust/dirt, server down, lightning, power outage, lost network connection, dead web service, hardware damage, human error, data theft, fire, earthquake, hacker attack. While there are 6 low level risks, namely backup failure, data corruption, overheat, overload, flooding and virus attacks. Therefore, this study concludes that there are no risks that are very dangerous or have a loss impact on companies related to the use of the SAP LOGON 750 application. Although there are medium-level risks, these can be overcome by technical and systematic risk treatment. Technical risk treatment includes reviewing ventilation and electrical structures, installing lightning rods, providing fire extinguishers, generators and UPS. While systematic risk treatment through periodic maintenance, among others, for servers, web services, networks, hardware and data backups. In addition, there is socialization and training for employees. PT XYZ is expected to always be vigilant and prepared by managing risks and risk treatment properly